3D Ordered Porous Hybrid of ZnSe/N‐doped Carbon with Anomalously High Na+ Mobility and Ultrathin Solid Electrolyte Interphase for Sodium‐Ion Batteries (Adv. Funct. Mater. 50/2021). (8th December 2021) - Li, Xueying; Han, Zhiyuan; Yang, Wenhua; Li, Qiang; Li, Hongsen; Xu, Jie; Li, Hongliang; Liu, Bing; Zhao, Haiguang; Li, Shandong; Wang, Xia; Wu, Xing‐Long
Abstract : Ultrathin Solid Electrolyte Interphase In article number 2106194, Shandong Li, Xia Wang, Xing‐Long Wu, and co‐workers design a 3D hierarchical porous ZnSe@N‐doped carbon hybrid as an anode material for sodium‐ion batteries, and simultaneously optimize electrolytes, resulting in rapid Na + diffusion kinetics and an ultrathin solid electrolyte interphase film.